A imagem do vinho: o caso da Quinta do Vesúvio (Região Demarcada do Douro – Douro Superior) - Sequeira, Carla; Lage, Otília (CEM – Cultura, Espaço & Memória, 2020)
Alongside the development of trade marks, following the Paris Convention (1883) and the Madrid Agreement (1891), the wine sector would develop actions to recognize and create legal mechanisms for defending the regional brand. After analyzing the evolution of the legal framework of brands and denominations of origin in the wine sector, from the end of the 19th century until today, we will reflect on the label as «construction of the image abroad»1. Based on a semiotic approach to the image of wines, a brief analysis is made of the Vesuvius brand of wines produced and marketed by Quinta do Vesuvio in the Upper Douro, from the observation of ideas, symbols and signs of composition of some images of their brand registers, stamps and labels, between 1847, 1863‑1902, 1913‑1936 and 2009. It is made a historical review of the famous wines, Moscatel and Porto, which remained in the local‑global history of this agro‑industrial exploration and presents the long history of this emblematic Quinta that gave its name to this wine brand of prestige and value to the important wine companies that owned it: D. Antónia A. Ferreira & Suc. and Companhia Agrícola e Comercial dos Vinhos do Porto, or still hold it today, since 1989, the Symington Family Estates.